Physical and molecular identification of fish and shrimp diseases in some farms of West Java, Banten and Jakarta, Indonesia - Adam Saba Anggara; Ida Ayu Mirah Meliana Dewi; Kismono Kudoasmoro; Putu Eka Sudaryatma; Putu Angga Wiradana (Jurnal Akuakultur Indonesia)
Infectious disease is a major challenge in fish and shrimp farming systems caused by microorganisms including bacteria, viruses and parasites. Physical detection has limitations in detecting diseases in cultivated animals earlier, because of the varied clinical symptoms. The aims of this study was to identify the physical and molecular presence of infectious pathogens in fish and shrimp cultivated in several ponds in West Java, Banten and Jakarta. Monitoring was carried out in two stages, namely the period March–April 2021 and September 2021 by taking samples from several ponds in Bogor, Tangerang, Depok and Jakarta. The sample criteria used were fish and shrimp showing normal and clinical symptoms of being attacked by a disease which were collected by purposive sampling. The collected samples were examined in two stages, namely physical examination of clinical symptoms and molecular examination using PCR. The results showed that of the 24 species samples collected, 17 species showed normal clinical symptoms and seven species showed clinical symptoms. Of the 24 fish and shrimp samples, four samples were infected (2 samples from normal species and 2 samples with clinical symptoms). The infected normal samples were Osphronemus goramy and Litopenaeus vannamei. The infected samples with clinical symptoms were Carassius auratus by Aeromonas salmonicida and red zebra cichlid (Metriaclima estherae) by Red Sea Bream Iridoviral Disease (RSBIV). Physical testing supported by molecular detection of aquatic animals can be an effort to manage aquaculture systems in Indonesia.